Reliability enhancement of radial distribution system by placing the reactive power compensators and distribution systems - Manjunatha Babu Pattabhi; Krishna Shanmukha Sundar; Bengaluru Rangappa Lakshmikantha (Bulletin of Electrical Engineering and Informatics, 2023)
Distribution systems (DSs) are highly stressed with addition of newer loads like electric vehicle charging stations and lower scope for expansion due to urbanization. Any line outage could cause interruption to major loads. Reliability studies have gained importance for lowering the frequency and lowering the duration of interruption for supply systems. In this paper a bi-stage method for optimum placement of reactive power compensation devices and distributed generations (DGs) for enhancing voltage stability and system reliability. A new method named delta analysis method is used to optimally locate the reactive power compensation devices and DGs. IEEE-33 radial DS, which is taken as experimental system. Based on the study, the fixing of reactive power compensation devices and DGs are to increase voltage outline of buses and decrease power fatalities. After the placement of DGs, the enhancement in reliability indices following line contingency is studied using MATLAB simulation.